Current Outlook of Ethnobotany in Bagmati Province, Central Nepal - Subedi, Dikshya; Bhattarai, Shreehari; Bhattarai, Suyog; Ghimire, Balkrishna (Journal of Plant Resources, 2025)
This paper reviews the state and prospects of ethnobotany in Bagmati Province, central Nepal, based on 102 studies identified through systematic searches using keywords like “ethnobotany,” “traditional knowledge,” and “indigenous knowledge.” The research employs a forward-backward reference searching approach to analyze 2,245 use reports for 557 plant species from 139 families, categorized into 15 use categories. The Fabaceae family was the most diverse (43 species), followed by Asteraceae (33 species) and Lamiaceae (27 species). Traditional medicine dominates plant use, accounting for 1,822 use reports. Regions such as Makwanpur (270 species), Sindhuli (149 species), and Dolakha (127 species) showed higher species diversity due to extensive field studies and ecological variation from subtropical lowlands to mid-hills. In contrast, high-altitude (Rasuwa, Sindhupalchok) and urbanized districts (Kathmandu) recorded fewer medicinal plants due to sparse populations and alternative healthcare access. Ethnicity-wise, the Newar (327) and Tamang (257) groups recorded the highest level of species diversity. The Brahmin and Chhetri groups, following a similar pattern, recorded 242 species However, Gurung, Pahari, Sarki, and Chepang recorded the least species. The larger ethnic groups documenting extensive usage and smaller groups preserving unique knowledge play an indispensable role in biodiversity conservation. This underscores the inter-relationship between ecological diversity, ethnic group distribution, and ethnobotanical knowledge. Integrating this traditional knowledge into national policies is important for conserving indigenous plant resources and fostering sustainability. Comprehensive surveys in underexplored areas, strengthening documentation, accreditation of traditional healers, and policy frameworks for drug development and quality assurance are vital for promoting ethnobotanical knowledge and its applications.